A Comparison of Food and Non-Food Enrichment with Zoo-Housed African Lions (Panthera leo) - Peggy Cremers; Max Norman; Sabrina Brando; Eduardo J. Fernandez (Journal of Zoological and Botanical Gardens, 2025)
Ongoing research on the effectiveness of enrichment at the species, group, and individual levels is beneficial to our growing understanding of animal welfare and behaviour for animals housed in human care. Diversifying the enrichment opportunities offered to animals in facilities such as zoos and aquariums helps to encourage a wide repertoire of species-typical, naturalistic, and rewarding behaviours. The present study aimed to examine the behavioural impact of novel food (ice blocks, gelatine, eggs) and non-food (lavender, clean sheets, mirrors) enrichment strategies on two zoo-housed prides of African lions (Panthera leo) housed in a rotation-based enclosure system at Orana Wildlife Park, New Zealand. The results of the study indicate that, while both forms of enrichment had a behavioural impact, the effects on behaviour varied with the type of enrichment used, both between and within the two categories. Different enrichment strategies varied in their impacts on resting behaviour, locomotion, and exploration levels in the lions. An increased focus on the specific behavioural outcomes of various novel enrichment strategies is essential to expand the efficacy of enrichment programs for future efforts to improve the wellbeing of zoo-housed animals.